Sampang Regency Government Strategy in Reconciliation of Sunni-Shia People - Adawiyah, Dwi Putri Robiatul; Zakirah, Dinda Marta Almas; Lestari, Dessy Dwi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
This study is intended to describe the government's propaganda strategy in reconciling followers of the Shi'a and Sunni sects in Sampang Regency. This research was conducted to find out how the government resolves the conflict between the two sects of Islam in Sampang Regency and the government's role in finding common ground between the two. This study uses a field research method that describes and presents the data descriptively. The results of this study indicate that the reconciliation propaganda strategy chosen by the government is a cultural strategy with cultural approaches. The strategy starts from affective aspects, cognitive aspects, and aspects. In addition, the government as a mediator absorbs and collects aspirations from below, both from ulema/kyai and Sunni community leaders and Shiite leaders.